Frequency of Immunisation of Children upto Five Years of Age According to Vaccination Card in Karachi - A Multicentre Study - Saba Siddiqui; Maham Akbar; Asma Mehtab; Maryam Zafar; Sonia Shahid; Shakeel Ahmed; Sina Aziz (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: To determine the frequency of immunisation of children upto 5 years of age according to vaccination card in the outpatient department of Abbasi Shaheed Hospital and Pakistan Naval Station  (PNS) Shifa, Bahria University Hospital Karachi. Methods:   A hospital based cross-sectional study was done for the period of two years from 2014 to 2016 in the Paediatric outpatient department (OPD) and vaccination center of Abbasi Shaheed Hospital and PNS Shifa Hospital. The study was done after the approval of ethical review board of Karachi Medical and Dental College (KM&DC).  Sampling  procedure  was  non-probability  convenience  sam-  pling. A total of 1408 children were included  in  study.  The  informed  valid  verbal  consent  was  taken from the parents before entering the data on pre designed vaccination charts  according  to  the  Ex-  panded Program of Immunisation (EPI) schedule. Data was entered after confirmation from child's vaccination card only. Data was analysed using SPSS version 20.0 for statistical analysis. Results: Out of 1408 children 53.8% were male, 46.2% females.  Age  of  the  children  was  0  to  60  weeks (5 years) out of which 73.0% were under one year of age. At birth, 46.3% received Bacille Calimette-Guerin (BCG) vaccine, 64.5% received both Oral Polio Vaccine (OPV) and Pentavalent 1 (Diphtheria, Pertussis, Tetanus,  Hep-B, H. influenza) at 6 weeks, 57.8% received OPV and Pentavalent       2 at 10 weeks, 56.4% received OPV and Pentavalent 3 at 14 weeks. Only 34.9% were vaccinated for measles at 9 months, which was reduced to 22.7% at 15 months. A total of 51.8% were completely vaccinated, 41.6% were incompletely vaccinated and 6.6% were unvaccinated. Conclusion: This study suggests that the rate of complete immunisation is still low and  there  are  drop-outs to the subsequent vaccines that needs immediate control. Moreover, about 40% of children appear incompletely vaccinated which is indeed an alarming situation.